Nitrogen-doped carbon material as well as preparation method and application thereof

By using hydrothermal reaction and pyrolysis methods in the preparation of nitrogen doped carbon materials, the problems of uneven distribution of nitrogen atoms and difficulty in controlling nitrogen content and specific surface area are solved, and the efficient potassium storage performance of nitrogen doped carbon materials is achieved.

CN119637844AActive Publication Date: 2025-03-18SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411780965.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-18
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing preparation methods of nitrogen doped carbon materials have uneven distribution of nitrogen atoms and it is difficult to quantitatively analyze the impact of nitrogen content and specific surface area on potassium storage performance.

Method used

A preparation method is adopted, including adding an acidic solution to the papermaking black liquid to obtain alkali lignin, followed by hydrothermal reaction and mixing with calcium chloride, drying and pyrolysis to obtain a nitrogen-doped carbon material. This method uniformly distributes nitrogen elements and accurately controls nitrogen content and specific surface area through hydrothermal grafting reaction and pyrolysis process.

Benefits of technology

The uniform distribution of nitrogen elements in the carbon framework and the precise control of nitrogen content and specific surface area are achieved, thereby quantitatively regulating the potassium storage performance of nitrogen-doped carbon materials, and improving the potassium storage capacity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637844A_ABST
    Figure CN119637844A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ion batteries, and discloses a nitrogen-doped carbon material as well as a preparation method and application thereof, and the preparation method of the nitrogen-doped carbon material comprises the following steps: (1) adding an acid solution into papermaking black liquid to obtain alkali lignin; (2) dissolving alkali lignin in a mixed solution of ammonia water and an organic solvent to obtain an alkali lignin solution; (3) carrying out hydrothermal reaction on the alkali lignin solution to obtain a pre-nitridation product; (4) mixing the pre-nitridation product with calcium chloride, drying and pyrolyzing to obtain a nitrogen-doped carbon material; the pyrolysis temperature is 400-800 DEG C, and the pyrolysis time is 3-5 hours. The nitrogen-doped carbon material is prepared by taking the papermaking black liquid as a biomass raw material, efficient utilization of wastes is effectively realized, nitrogen elements in the nitrogen-doped carbon material are uniformly distributed in a carbon skeleton, and the nitrogen content and the specific surface area of the nitrogen-doped carbon material can be accurately controlled through a pyrolysis process; furthermore, the potassium adsorption and storage behavior of the nitrogen-doped carbon material is quantitatively controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ion batteries, and in particular to a nitrogen-doped carbon material and a preparation method and application thereof. Background Art

[0002] In recent years, lithium-ion batteries have been widely used due to their high energy density and safety, especially in portable mobile devices and electric vehicles. However, due to the relatively limited lithium resources, the rapid rise in its price has caused significant restrictions on the long-term application of lithium batteries. Therefore, there is an urgent need to develop new energy storage batteries with more abundant reserves and lower prices to supplement and replace lithium-ion batteries. Potassium-ion batteries have become a potential supplement and substitute for lithium-ion batteries due to their low cost and high energy density. Potassium ions can be embedded in the graphite structure to form intercalation compounds with a theoretical capacity of up to 279mAh / g, so carbon materials are regarded as the most promising negative electrode materials for potassium-ion batteries. However, compared with lithium ions, the larger size of potassium ions causes significant volume expansion of graphite materials during charging and discharging, and the reaction kinetics are slower.

[0003] In contrast, non-graphite carbon materials with less graphite structure generally exhibit better potassium storage capacity, which is attributed to their rich defect structure and large specific surface area, which can provide adsorption behavior in addition to intercalation behavior. The introduction of nitrogen atoms into the carbon skeleton can effectively increase the disorder of carbon materials and increase active sites, thereby improving their potassium storage performance. At present, the conventional preparation method of biomass-based nitrogen-doped carbon materials is to mix biomass with nitrogen-containing compounds and then pyrolyze them. Although this physical mixing method can successfully prepare nitrogen-doped carbon materials, there is a problem of uneven distribution of nitrogen atoms. In addition, the precise control of nitrogen content and specific surface area is also challenging, which makes it difficult to quantitatively analyze the effects of these two key factors, nitrogen content and specific surface area, on potassium storage performance. Summary of the invention

[0004] In view of this, the present invention provides a nitrogen-doped carbon material, a preparation method thereof, and an application thereof in a potassium ion battery, so as to solve the problem that the existing preparation method of nitrogen-doped carbon material has uneven distribution of nitrogen atoms, and the existing preparation method of nitrogen-doped carbon material is difficult to quantitatively analyze the influence of nitrogen content and specific surface area on potassium storage performance.

[0005] In order to solve the above-mentioned technical problems, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides a method for preparing a nitrogen-doped carbon material, comprising the following steps:

[0007] (1) adding an acidic solution to papermaking black liquor to obtain alkaline lignin;

[0008] (2) dissolving the alkali lignin in a mixed solution of ammonia water and an organic solvent to obtain an alkali lignin solution;

[0009] (3) subjecting the alkaline lignin solution to a hydrothermal reaction to obtain a pre-nitrogenated product;

[0010] (4) mixing the pre-nitridation product with calcium chloride, drying and pyrolyzing to obtain a nitrogen-doped carbon material;

[0011] The pyrolysis temperature is 400-800° C., and the pyrolysis time is 3-5 hours.

[0012] Preferably, in step (2), the ratio of the alkali lignin to the mixed solution of ammonia water and organic solvent is (1-10) g:100 mL.

[0013] Preferably, the volume ratio of ethanol to ammonia water in the mixed solution of ammonia water and organic solvent is 1:(2-4);

[0014] Preferably, the concentration of the aqueous ammonia is 20-28%.

[0015] Preferably, the temperature of the hydrothermal reaction in step (3) is 100-120° C., and the time of the hydrothermal reaction is 6-12 h.

[0016] Preferably, the mass ratio of the calcium chloride to the alkali lignin in step (4) is 1-3:1

[0017] On the other hand, the present invention provides a nitrogen-doped carbon material prepared by any of the preparation methods described above.

[0018] In addition, the present invention also provides a nitrogen-doped carbon material prepared by any of the preparation methods described above or the use of the nitrogen-doped carbon material in a potassium ion battery.

[0019] The present invention provides a nitrogen-doped carbon material and a preparation method and application thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention utilizes the property that papermaking black liquor contains alkali lignin. After adding an acidic solution into the papermaking black liquor, the alkali lignin therein is precipitated and then undergoes a hydrothermal reaction, and then is pyrolyzed after adding calcium chloride. During the pyrolysis process, the carbon material is catalyzed to graphitize, and the pores of the carbon material are expanded, so as to finally obtain a nitrogen-doped carbon material.

[0021] The nitrogen element in the nitrogen-doped carbon material prepared by the method of the present invention is evenly distributed in the carbon skeleton through a hydrothermal grafting reaction, and the nitrogen content and specific surface area of ​​the nitrogen-doped carbon material can be accurately controlled through the pyrolysis process, thereby quantitatively controlling the potassium adsorption and storage behavior of the nitrogen-doped carbon material. In addition, the present invention uses papermaking black liquor as a biomass raw material to prepare the nitrogen-doped carbon material, thereby realizing the efficient utilization of waste papermaking black liquor. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0023] Figure 1 is a quantitative relationship diagram between the nitrogen content and specific surface area of ​​the nitrogen-doped carbon material of the present invention and the pyrolysis temperature;

[0024] Figure 2 This is the SEM spectrum of the nitrogen-doped carbon material of Example 1 of the present invention;

[0025] Figure 3 This is a schematic diagram of the TEM mapping test results of the nitrogen-doped carbon material of Example 1 of the present invention;

[0026] Figure 4 This is a schematic diagram of the cycle performance of the nitrogen-doped carbon material of Example 1 of the present invention as a negative electrode material for a potassium ion battery under the condition of 100 mA / g;

[0027] Figure 5 A schematic diagram of the cycle performance of the doped carbon material prepared in Example 1 of the present invention as a negative electrode material for a potassium ion battery under the condition of 2000 mA / g;

[0028] Figure 6 This is a schematic diagram of the cycle performance of the nitrogen-doped carbon material of Example 2 of the present invention as a negative electrode material for a potassium ion battery under the condition of 100 mA / g;

[0029] Figure 7 This is a schematic diagram of the cycle performance of the nitrogen-doped carbon material of Example 5 of the present invention as a negative electrode material for a potassium ion battery under the condition of 100 mA / g;

[0030] Figure 8 This is a schematic diagram of the cycle performance of the nitrogen-doped carbon material of Comparative Example 1 of the present invention as a negative electrode material for a potassium ion battery under the condition of 100 mA / g;

[0031] Fig. 9This is a relationship diagram between the pyrolysis temperature and the discharge capacity and adsorption ratio of the nitrogen-doped carbon material of the present invention;

[0032] Fig.10 It is a linear relationship diagram of the ratio of nitrogen content to specific surface area and adsorption proportion of the nitrogen-doped carbon material of the present invention. DETAILED DESCRIPTION

[0033] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.

[0034] In one aspect of the present invention, the present invention provides a method for preparing a nitrogen-doped carbon material, comprising the following steps:

[0035] (1) Add an acidic solution to papermaking black liquor to obtain alkaline lignin.

[0036] In some embodiments of the present invention, the step is specifically to continuously add an acidic solution to the papermaking black liquor under stirring conditions until the pH is less than 3, at which time the alkali lignin in the papermaking black liquor is fully precipitated. It has been found through experiments that the yield of alkali lignin precipitation reaches a peak when the pH reaches 3.

[0037] In some embodiments of the present invention, the papermaking black liquor from which alkali lignin is precipitated is filtered to obtain a filter cake, the filter cake is washed with deionized water to remove the salt therein, and dried in a blast drying oven to obtain alkali lignin. In some embodiments of the present invention, the drying temperature is 105-120° C., for example, 105° C., 110° C., 115° C., 120° C., etc., and the drying time is 12-48 hours, for example, 12 hours, 18 hours, 24 hours, 32 hours, 48 ​​hours, etc.

[0038] In some embodiments of the present invention, the acidic solution is added to the papermaking black liquor under stirring. The acidic solution may be hydrochloric acid, sulfuric acid, etc. Since the acidic solution here is only used to adjust the pH value, there is no special limitation on the type and concentration of the acidic solution, which can be adjusted according to actual conditions.

[0039] Papermaking black liquor is a waste biomass produced in the papermaking process, which contains a large amount of alkali lignin, has a large annual output, is concentrated in distribution, and has no good treatment method. Based on this, the present invention uses papermaking black liquor as a biomass raw material as a precursor for preparing non-graphite carbon to achieve efficient utilization of waste. The papermaking black liquor used in the embodiment of the present invention is wastewater from a paper mill, and its main components are alkali and alkali lignin. Since the main purpose of the present invention is to precipitate alkali lignin in papermaking black liquor, other components of papermaking black liquor are not particularly limited.

[0040] (2) dissolving the alkali lignin in a mixed solution of ammonia water and an organic solvent to obtain an alkali lignin solution.

[0041] In some embodiments of the present invention, the ratio of the alkali lignin to the mixed solution of ammonia water and organic solvent is (1-10) g:100 mL, for example, 1 g:100 mL, 2 g:100 mL, 5 g:100 mL, 8 g:100 mL, 10 g:100 mL, etc. In some embodiments of the present invention, the volume ratio of the organic solvent to the ammonia water in the mixed solution of ammonia water and organic solvent is 1:(2-4), for example, 1:2, 1:3, 1:4, etc. The concentration of the ammonia water is 20-28%, for example, 20%, 22%, 24%, 26%, 28%, etc. The present invention uses the mixed solution of ammonia water and organic solvent as the solvent of alkali lignin, wherein the role of ammonia water is to undergo a grafting reaction with the alkali lignin to provide a nitrogen source for nitrogen doping, and the organic solvent can be ethanol, acetone, etc., as a co-solvent to accelerate the dissolution of the alkali lignin.

[0042] (3) The alkaline lignin solution is subjected to a hydrothermal reaction to obtain a pre-nitrogenated product.

[0043] In some embodiments of the present invention, this step specifically involves transferring the alkali lignin solution to a stainless steel autoclave for hydrothermal reaction. It should be noted that the hydrothermal reaction process can utilize the pressure generated by the hydrothermal process without additional pressurization.

[0044] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 100-120°C, for example, 100°C, 110°C, 120°C, etc.; the time of the hydrothermal reaction is 6-12h, for example, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.

[0045] (4) The pre-nitridation product is mixed with calcium chloride, and the mixture is dried and pyrolyzed to obtain a nitrogen-doped carbon material.

[0046] In some embodiments of the present invention, before mixing the pre-nitridation product with the calcium chloride, the step further includes: adjusting the pH value of the pre-nitridation product to less than 7 to prevent the calcium chloride from reacting to form calcium hydroxide. In some embodiments of the present invention, this step specifically includes transferring the pre-nitridation product to a container such as a beaker, adding an acidic solution to adjust the pH value to less than 7, then adding calcium chloride, dissolving it, and then drying it in an oven, and then placing the dried pre-nitridation product in a tubular furnace for pyrolysis to obtain a nitrogen-doped carbon material.

[0047] In some embodiments of the present invention, the mass ratio of calcium chloride to alkali lignin is 1-3:1, for example, it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, etc. By adding calcium chloride, the carbon material can be catalyzed to graphitize during the pyrolysis process and more mesopores can be formed.

[0048] In some embodiments of the present invention, the drying temperature is 105-120°C, for example, 105°C, 110°C, 115°C, 120°C, etc., and the drying time is 12-24h, for example, 12h, 15h, 20h, 24h, etc.

[0049] In some embodiments of the present invention, the pyrolysis temperature is 400-800°C, and the pyrolysis time is 3-5h. The pyrolysis temperature may be, for example, 400°C, 500°C, 600°C, 700°C, 800°C, etc., and the pyrolysis time may be, for example, 3h, 4h, 5h, etc. By adjusting the pyrolysis temperature, the nitrogen content and specific surface area of ​​the nitrogen-doped carbon material can be precisely controlled, thereby quantitatively controlling the nitrogen-doped carbon material's adsorption and potassium storage behavior.

[0050] The present invention has no particular limitation on the heating rate to the pyrolysis temperature, which can be any rate. In the embodiment of the present invention, the heating rate is 5°C / min.

[0051] In some embodiments of the present invention, after the pyrolysis is completed, the following steps are further included: washing and drying the pyrolysis product. The washing can be performed with deionized water and ethanol for 3-5 times, for example, 3 times, 4 times or 5 times, the drying temperature is 105-120°C, for example, 105°C, 110°C, 115°C, 120°C, etc., and the drying time is 12-24h, for example, 12h, 15h, 20h, 24h, etc.

[0052] On the other hand, the present invention provides a nitrogen-doped carbon material prepared by any of the preparation methods described above. Since the nitrogen-doped carbon material is prepared by the aforementioned method, the nitrogen-doped carbon material has all the characteristics and advantages of the aforementioned method, which will not be repeated here.

[0053] In the present invention, the nitrogen content of the nitrogen-doped carbon material is 4-10%.

[0054] In addition, the present invention also provides a nitrogen-doped carbon material prepared by any of the preparation methods described above or the use of the nitrogen-doped carbon material in a potassium ion battery.

[0055] The technical scheme of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. The embodiments of the present application are only used as examples, and all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0056] Example 1

[0057] This embodiment provides a method for preparing a nitrogen-doped carbon material, which is carried out according to the following steps:

[0058] (1) 100 mL of papermaking black liquor was placed in a beaker, and concentrated hydrochloric acid was continuously added at a speed of 800 rpm until the pH value was less than 3, and alkali lignin was fully precipitated. The papermaking black liquor with precipitated alkali lignin was filtered to obtain a filter cake, and the filter cake was washed with deionized water, and then dried in a 110° C. forced air drying oven for 24 h to obtain alkali lignin;

[0059] (2) adding 5 g of the alkali lignin obtained in step (1) to a mixed solution of 20 mL of ethanol and 80 mL of concentrated aqueous ammonia, and stirring continuously until completely dissolved to obtain an alkali lignin solution;

[0060] (3) transferring the alkaline lignin solution to a stainless steel high-pressure reactor, keeping the temperature at 120° C. for 12 h, and performing a hydrothermal reaction to obtain a pre-nitrogenated product;

[0061] (4) Transfer the pre-nitrogenated product to a beaker, continue to add concentrated hydrochloric acid to the beaker until the pH value is less than 7, then add 10 g of calcium chloride, dissolve it and place it in an oven at 120° C. to dry for 48 hours;

[0062] (5) placing the dried product of step (4) in a tubular furnace for pyrolysis carbonization, heating from room temperature to pyrolysis temperature at a rate of 5°C / min, the pyrolysis temperature is 600°C, and the pyrolysis time is 3h;

[0063] (6) The pyrolysis product of step (5) was washed with deionized water and ethanol three times each, and dried at 105° C. for 12 h to obtain a nitrogen-doped carbon material.

[0064] Example 2

[0065] This embodiment is basically the same as embodiment 1, the only difference being that the pyrolysis temperature in step (5) is 400°C.

[0066] Example 3

[0067] This embodiment is basically the same as embodiment 1, the only difference being that the pyrolysis temperature in step (5) is 500°C.

[0068] Example 4

[0069] This embodiment is basically the same as embodiment 1, the only difference being that the pyrolysis temperature in step (5) is 700°C.

[0070] Example 5

[0071] This embodiment is basically the same as embodiment 1, the only difference being that the pyrolysis temperature in step (5) is 800°C.

[0072] Figure 1 The figure shows the quantitative relationship between the nitrogen content and specific surface area of ​​nitrogen-doped carbon materials and the pyrolysis temperature. It can be seen from the figure that under the pyrolysis temperatures of 400°C, 500°C, 600°C, 700°C, and 800°C, the nitrogen content of the carbon materials is 9.36%, 7.82%, 6.33%, 4.78%, and 4.07%, respectively, and the specific surface area is 127m 2 / g, 225m 2 / g, 335m 2 / g, 441m 2 / g, 523m 2 / g. The nitrogen content and specific surface area both show an accurate linear relationship with the pyrolysis temperature, indicating that the nitrogen content and specific surface area of ​​the nitrogen-doped carbon material can be accurately controlled by adjusting the pyrolysis temperature using the method of the present invention.

[0073] Figure 2 This is the SEM image of the nitrogen-doped carbon material obtained in Example 1. It can be seen from the figure that the nitrogen-doped carbon material is agglomerated by irregular carbon blocks and has abundant morphological defects on the surface, which is beneficial to the improvement of battery performance.

[0074] Figure 3 This is the mapping test result of the nitrogen-doped carbon material obtained in Example 1. It can be seen from the figure that the nitrogen element in the nitrogen-doped carbon material is evenly distributed in the carbon skeleton.

[0075] Comparative Example 1

[0076] This comparative example is basically the same as Example 1, with the only difference being that step (3) is omitted, i.e. the alkaline lignin solution is not subjected to hydrothermal reaction.

[0077] Application Examples

[0078] The nitrogen-doped carbon materials prepared in Example 1, Example 2, Example 5 and Comparative Example 1 were mixed with a conductive agent and polyvinylidene fluoride in a mass ratio of 8: 1: 1, methyl pyrrolidone was added to mix into a uniform slurry, and then evenly coated on a copper foil by a coating method, and punched into a circular electrode sheet after being fully dried, and assembled into a button battery in a glove box. The assembly conditions are: metallic potassium is used as the counter electrode, 1 mol / L KN (SO2F) 2 ethylene carbonate and diethyl carbonate mixed solution (volume ratio 1: 1) is used as the electrolyte, and glass fiber GF / D is used as a diaphragm. After standing for 1 hour, a constant current charge and discharge test is performed in a CT3001A blue battery test system, and the voltage range is 0.01-3V.

[0079] Figure 4 When the nitrogen-doped carbon material obtained in Example 1 is used as the negative electrode material of a potassium ion battery, the cycle performance under 100 mA / g conditions can be seen from the figure that after 200 cycles, the discharge capacity of the nitrogen-doped carbon material can still reach 467.3 mAh / g, and the capacity retention rate is 97.95%.

[0080] Figure 5 When the nitrogen-doped carbon material obtained in Example 1 is used as the negative electrode material of a potassium ion battery, the cycle performance under 2000 mA / g conditions can be seen from the figure that after 5000 cycles, the discharge capacity of the nitrogen-doped carbon material can still reach 183.7 mAh / g / , and the capacity retention rate is 89.9%.

[0081] Figure 6 When the nitrogen-doped carbon material obtained in Example 2 is used as the negative electrode material of the potassium ion battery, the cycle performance under the condition of 100 mA / g can be seen from the figure that after 200 cycles, the discharge capacity of the nitrogen-doped carbon material can still reach 295.6 mAh / g, and the capacity retention rate is 96.74%.

[0082] Figure 7 When the nitrogen-doped carbon material obtained in Example 5 is used as the negative electrode material of the potassium ion battery, the cycle performance under the condition of 100 mA / g can be seen from the figure that after 200 cycles, the discharge capacity of the nitrogen-doped carbon material can still reach 183.2 mAh / g, and the capacity retention rate is 97.82%.

[0083] Figure 8 The cycle performance of the non-nitrogen-doped carbon material obtained in Comparative Example 1 as the negative electrode material of a potassium ion battery under the condition of 100 mA / g. As can be seen from the figure, after 200 cycles, the discharge capacity of the material is only 76.8 mAh / g, and the capacity retention rate is 56.63%. This shows that nitrogen doping can effectively increase the defect sites of the material and improve the adsorption capacity of potassium ions.

[0084] Fig. 9This is a relationship diagram between the pyrolysis temperature of the present invention and the discharge capacity and adsorption ratio of the nitrogen-doped carbon material. It can be seen from the figure that with the increase of the pyrolysis temperature, the adsorption ratio of the nitrogen-doped carbon material gradually decreases and presents a certain linear relationship, and both the intercalation capacity and the adsorption capacity show a trend of first increasing and then decreasing. The discharge capacity is optimal when the pyrolysis temperature is 600°C.

[0085] Fig.10 The ratio of the nitrogen content and specific surface area of ​​the nitrogen-doped carbon material of the present invention and the adsorption ratio show a linear relationship, indicating that the present invention can quantitatively control the adsorption behavior of potassium ions.

[0086] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a nitrogen-doped carbon material, characterized in that: The following steps are involved: (1) adding an acidic solution to papermaking black liquor to obtain alkaline lignin; (2) dissolving the alkali lignin in a mixed solution of ammonia water and an organic solvent to obtain an alkali lignin solution; (3) subjecting the alkaline lignin solution to a hydrothermal reaction to obtain a pre-nitrogenated product; (4) mixing the pre-nitridation product with calcium chloride, drying and pyrolyzing to obtain a nitrogen-doped carbon material; The pyrolysis temperature is 400-800° C., and the pyrolysis time is 3-5 hours.

2. The method for preparing the nitrogen-doped carbon material according to claim 1, characterized in that: In step (2), the ratio of the alkali lignin to the mixed solution of ammonia water and organic solvent is (1-10) g:100 mL.

3. The method for preparing the nitrogen-doped carbon material according to claim 1, characterized in that: The volume ratio of the organic solvent to the ammonia water in the mixed solution of the ammonia water and the organic solvent is 1:(2-4).

4. The method for preparing a nitrogen-doped carbon material according to any one of claims 1 to 3, characterized in that: The mass concentration of the ammonia water is 20-28%.

5. The method for preparing the nitrogen-doped carbon material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (3) is 100-120° C., and the time of the hydrothermal reaction is 6-12 hours.

6. The method for preparing the nitrogen-doped carbon material according to claim 1, characterized in that: The mass ratio of the calcium chloride to the alkali lignin in step (4) is 1-3:

1.

7. The method for preparing a nitrogen-doped carbon material according to any one of claims 1 to 6, characterized in that: Before mixing the pre-nitridation product with the calcium chloride in step (4), the method also includes: adjusting the pH value of the pre-nitridation product to be less than 7.

8. A nitrogen-doped carbon material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the nitrogen-doped carbon material prepared by the preparation method according to any one of claims 1 to 7 or the nitrogen-doped carbon material according to claim 8 in a potassium ion battery.

Citation Information

Patent Citations

  • Lignin-based transition metal / nitrogen doped carbon material, and preparation and application thereof

    CN109012590A

  • Preparation method and application of FeMoS catalyst for microwave-assisted catalytic de-polymerization of lignin

    CN111233941A

  • Monatomic catalyst taking nitrogen-doped lignin carbon dots as carrier and application of monatomic catalyst

    CN114887641A

  • Nitrogen-doped porous carbon material and preparation method and use thereof

    US20240140800A1